Temperature changes over storms from measurements of spacecraft TIMED - Pylypenko, S.; Motsyk, O.; Kozak, L. (Advances in Astronomy and Space Physics, 2016)
In the present work we have studied changes of mesospheric temperature over the powerful storms Wilma, Haitang, and Katrina using measurements of the space vehicle TIMED. We have found the temperature increasing at the altitude range 80-100 km. We have found the explanations for the obtained results by the dissipation of the gravity waves. Propagation of atmospheric gravity waves in a non-isothermal, windless atmosphere, with taking into account the viscosity and the thermal conductivity, has also been modelled in this work. We have determined that the maximum of amplitude of the atmospheric-gravity waves at the considered characteristics corresponds to altitudes of near 90 km (mesopause). It was found that the main factor influencing propagation and dissipation of the wave in such cases is the vertical temperature gradient. Viscosity and thermal conductivity have less influence on the wave amplitude.